Systematic literature review : the important factors in assessing the trustworthiness of OSS. - Md. Sultan, Abu Bakar; Diwani Bakar, Abubakar; Zulzalil, Hazura; Din, Jamilah (Praise Worthy Prize, 2013)
Background: Trustworthiness takes an important attention in software development paradigm. It is one of the important aspects in software adaptation. This confidence characteristic works more closely in OSS development paradigm where development practice is more abstract. Aims: This paper is set out to examine the factors in the evaluation of trustworthiness of open source software Method: This systematic literature review surveyed the articles published between 2007 and 2012 in five most repository of research paradigm. The results: The study identified the reliability and interoperability as the top most important factors for the OSS practitioners to take into consideration in their software adaptation. Conclusion: The study discusses the systematic literature review on how to identify the trustworthiness of the open source software and find out that reliability is the highest ranking factors that is needed to be considered in the adoption of the software. Further theoretical and empirical research is still needed on this area. Researchers can work more in this area by validating these findings empirically to gain more facts about this area.